Polityka ilości i jakości oraz zadłużenia w konkurencyjnym zarządzaniu wybranych przedsiębiorstw przemysłu mięsnego - Zuba, Jan; Zuba, Maria (Policy of Quantity, Quality and Liabilities in Competitive Management of Chosen Meat Enterprises, 2006)
An elaboration points at making an impact analysis of basic management determinants: quality, quantity and liabilities on the level of competing effectiveness in two meat enterprises. Competing effectiveness was measured by economic and financial capacity. The survey concerns two noncommercial partnerships within six years. The first enterprise in comparison with the second one gained 3,9 times higher commerce capacity, two times lower assets productivity and 2,6 times lower liabilities coefficient. Taking this information into account this enterprise gained about 74,2% higher economic capacity and about 22,9% higher financial capacity in comparison with the second enterprise. Recapitulating the first enterprise used quality policy in the competition process but the second enterprise used quantity and liabilities policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 559-563